Key building blocks for high-capacity WDM photonic transport networks. - Jourdan, A.
The objective of this paper is to give an overview of the different studies we have performed at the research level regarding the design and implementation of a photonic wavelength division multiplexing (WDM) layer providing transparent transport services to client layers (SONET/SDH, ATM, etc.). Such a network requires a number of enabling factors to be assessed in order to become a reality. Among these factors are the availability of high-capacity WDM transmission systems and efficient optical routing nodes based on mature technology, the design of robust networks optimizing the utilization of resources, and the development of a management system in accordance with presently applied standards for transport networks. We review our achievements in these different fields
Keywords: ATM; SONET/SDH.; Building blocks; Client layers; High-capacity WDM photonic transport networks; Management system; Optical routing nodes; Photonic wavelength division multiplexing; Research; Robust network design; Standards; Transparent transport services